THE EFFECT OF MIDWIVES’ COMMUNICATION ON PREGNANT WOMEN’S SATISFACTION WITH ANTENATAL CARE - Yuliwati Yuliwati (International Journal of Multidisciplinary Research and Literature, 2025)
Midwife communication is one of the important factors in antenatal care (ANC) services because it can affect pregnant women's understanding, comfort, and satisfaction with the services received. Effective communication can create a relationship of mutual trust between midwives and pregnant women so as to improve the quality of midwifery services. Pregnant women's satisfaction with ANC services is an important indicator in the success of maternal health services. The purpose of this study aims to analyze the influence of midwifery communication on the satisfaction of pregnant women in antenatal care services based on the results of published research. This research method uses the Systematic Literature Review (SLR) method. The article search was conducted through Google Scholar and PubMed databases with the keywords "midwife communication", "pregnant woman satisfaction", and "antenatal care". The articles used are national and international articles published in 2020–2025 in accordance with inclusion and exclusion criteria. Analysis was carried out on articles that met the research criteria. Results; The results of the review showed that midwife's communication had a significant influence on the satisfaction of pregnant women in antenatal care services. Good, empathetic, clear, and easy-to-understand communication can increase the comfort, trust, and compliance of pregnant women in conducting ANC visits. Most studies show a significant association with p-values <0.05. Conclusion; Midwifery communication affects the level of satisfaction of pregnant women with antenatal care services. The better the communication provided by the midwife, the higher the level of satisfaction of pregnant women with the services received.